CytoSorb Rescue for COVID-19 Patients With Vasoplegic Shock and Multiple Organ Failure: A Prospective, Open-Label, Randomized Controlled Pilot Study*. Issue 6 (9th February 2022) - Stockmann, Helena; Thelen, Philipp; Stroben, Fabian; Pigorsch, Mareen; Keller, Theresa; Krannich, Alexander; Spies, Claudia; Treskatsch, Sascha; Ocken, Michele; Kunz, Julius Valentin; Krüger, Anne; Khadzhynov, Dmytro; et al.
Abstract : OBJECTIVES: To investigate the effect of extracorporeal cytokine reduction by CytoSorb (CytoSorbents, Monmouth Junction, NJ) on COVID-19–associated vasoplegic shock. DESIGN: Prospective, randomized controlled pilot study. SETTING: Eight ICUs at three sites of the tertiary-care university hospital Charité—Universitätsmedizin Berlin. PATIENTS: COVID-19 patients with vasoplegic shock requiring norepinephrine greater than 0.2 µg/kg/min, C-reactive protein greater than 100 mg/L, and indication for hemodialysis. INTERVENTIONS: Randomization of 1:1 to receive CytoSorb for 3–7 days or standard therapy. To account for inadvertent removal of antibiotics, patients in the treatment group received an additional dose at each adsorber change. MEASUREMENTS AND MAIN RESULTS: The primary endpoint was time until resolution of vasoplegic shock, estimated by Cox-regression. Secondary endpoints included mortality, interleukin-6 concentrations, and catecholamine requirements. The study was registered in the German Registry of Clinical Trials (DRKS00021447). From November 2020 to March 2021, 50 patients were enrolled. Twenty-three patients were randomized to receive CytoSorb and 26 patients to receive standard of care. One patient randomized to cytokine adsorption was excluded due to withdrawal of informed consent. Resolution of vasoplegic shock was observed in 13 of 23 patients (56.5%) in the CytoSorb and 12 of 26 patients (46.2%) in the control group after a median of 5 days (interquartile range [IQR], 4–5 d) and 4 days (IQR, 3–5 d). The hazard ratio (HR) for the primary endpoint, adjusted for the predefined variables age, gender, extracorporeal membrane oxygenation-therapy, or time from shock onset to study inclusion was HR, 1.23 (95% CI, 0.54–2.79); p = 0.63. The mortality rate was 78% in the CytoSorb and 73% in the control group (unadjusted HR, 1.17 [95% CI, 0.61–2.23]; p = 0.64). The effects on inflammatory markers, catecholamine requirements, and the type and rates of adverse events were similar between the groups. CONCLUSIONS: In severely ill COVID-19 patients, CytoSorb did not improve resolution of vasoplegic shock or predefined secondary endpoints.